2002
DOI: 10.2139/ssrn.313190
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Market Liberalization on the Relative Earnings of Chinese Women

Abstract: In this paper we first explore the effects of differences in labor market institutions and the degree of market liberalization on the size and composition of gender wages gaps in China's urban labor markets. We use enterprise-ownership type, enterprise age, and workers' methods of finding employment as proxies for the extent of market liberalization. We find both the size of the wage gaps and the proportion of the gap left unexplained by differences in productive characteristics largest in the most liberalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 24 publications
9
53
0
Order By: Relevance
“…A recent study by Kanbur and Zhang (2005) analyzed Chinese provincial inequality for the period 1952–2000 and concluded that provincial inequality in China has consistently risen since the reforms, and that a substantial inland–coastal inequality has existed since the late 1980s. Their findings are in line with the results of earlier studies indicating that regional disparity was strongly associated with the implementation of economic reforms (Gustafsson and Li, 2000; Maurer‐Fazio and Hughes, 2002; Song et al ., 2000; Zhang and Zhang, 2003).…”
Section: Introductionsupporting
confidence: 92%
See 4 more Smart Citations
“…A recent study by Kanbur and Zhang (2005) analyzed Chinese provincial inequality for the period 1952–2000 and concluded that provincial inequality in China has consistently risen since the reforms, and that a substantial inland–coastal inequality has existed since the late 1980s. Their findings are in line with the results of earlier studies indicating that regional disparity was strongly associated with the implementation of economic reforms (Gustafsson and Li, 2000; Maurer‐Fazio and Hughes, 2002; Song et al ., 2000; Zhang and Zhang, 2003).…”
Section: Introductionsupporting
confidence: 92%
“…Furthermore, one could argue that the decomposition methods proposed by Neumark (1988) or Cotton (1988) may also be relevant. Studies of Jolliffe and Campos (2005), Maurer‐Fazio and Hughes (2002), and Liu et al . (2000) are among the examples of studies taking this approach.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations